The role of the FtsH protease in the repair of Photosystem II after damage by UV-B radiation in Synechocystis 6803 - Cheregi, Otilia (Acta Biologica Szegediensis, 2005)
We have investigated the repair mechanism of UV-damaged PSII in Synechocystis 6803 cells, in relation to the role of the FtsH protease. FtsH is an ATP- dependent metalloprotease that belongs to the AAA- ( ATP-ase associated with diverse cellular activities) protein family. One of the homologues is encoded by the slr0228 gene whose transcript level is induced 16 fold by UV-B radiation. The UV-B induced loss of oxygen evolving activity was accelerated in the ΔFtsH mutant, which lacks the FtsH protease due to the deletion of the slr0228 gene. In the presence of the protein synthesis inhibitor lincomycin, the rate of UV-B induced oxygen inhibition in the ΔFtsH mutant show the same kinetics as in the absence of antibiotic. In addition, the mutation completely abolished the restoration of oxygen evolution in visible light following UV-B treatment. These data demonstrate that PSII repair is blocked in the absence of the FtsH protease both under UV illumination and in visible light following the UV-B treatment.